2013
DOI: 10.1039/c3cp43938k
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in biomedical applications of titanium dioxide

Abstract: As one of the most common chemical materials, titanium dioxide (TiO2) has been prepared and widely used for many years. Among all the applications, the biomedical applications of TiO2 have motivated strong interest and intensive experimental and theoretical studies, owing to its unique photocatalytic properties, excellent biocompatibility, high chemical stability, and low toxicity. Advances in nanoscale science suggest that some of the current problems of life science could be resolved or greatly improved thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
121
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(138 citation statements)
references
References 129 publications
0
121
0
1
Order By: Relevance
“…Titanium oxide (TiO 2 ) has a wide range of biomedical applications (Fei Yin et al 2013). For instance, in bone-substituting materials, the biofluid first makes contact with a thin TiO 2 layer that spontaneously emerges on the top surface of metallic titanium (Hanawa 2011;Feng et al 2003).…”
Section: Biomedical Applications Of Metal Oxide Nanoparticlesmentioning
confidence: 99%
“…Titanium oxide (TiO 2 ) has a wide range of biomedical applications (Fei Yin et al 2013). For instance, in bone-substituting materials, the biofluid first makes contact with a thin TiO 2 layer that spontaneously emerges on the top surface of metallic titanium (Hanawa 2011;Feng et al 2003).…”
Section: Biomedical Applications Of Metal Oxide Nanoparticlesmentioning
confidence: 99%
“…In this line, nano-particles, such as metallic NPs, ceramic NPs, and quantum dots could help improve PDT of cancer (7). In particular, experimental results showed that TiO 2 NPs could be an excellent PS in PDT of cancer due to their unique properties, such as strong optical absorption, high chemical stability, and non-toxicity (8,9). Low concentrations of TiO 2 NPs did not show significant toxicity by themselves yet, irradiation of these NPs by ultraviolet (UV) light could lead to generation of ROS and consequently cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles (NPs) are used ubiquitously in food, medicine, military, construction, cosmetics and sports [2]. Titanium dioxide NPs (TDNPs), in particular, are considered vital in the development of antimicrobiotic applications [3,4]. However, there are increasing concerns that nanotechnology may threaten our health [1].…”
Section: Introductionmentioning
confidence: 99%
“…Anatase TDNPs are common NPs being used for many purposes such as antibacterial effects, sunscreens and cosmetics, making use of their photodynamic properties [4]. The toxic potential of TDNPs is unclear in the presence and absence of ultraviolet (UV) irradiation.…”
Section: Introductionmentioning
confidence: 99%